A MODERN DESCENDING TREND IN THE PERSPECTIVE OF THE PARTY SYSTEM DEVELOPMENT OF UKRAINE - Білоус, Л. В.; Макаровський, І. П. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article deals with the descending trend from the system of medium parties toward the system of small parties, which is connected with the parliamentary elections in 2014 analyzed in the perspective of the party system development of Ukraine.